2007
DOI: 10.1177/1045389x06073640
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damage Detection in the Frequency Domain using Neural Networks

Abstract: A bi-level damage detection algorithm that utilizes dynamic responses of the structure as input and neural network (NN) as a pattern classifier is presented. The signal anomaly index (SAI) is proposed to express the amount of changes in the shape of frequency response functions (FRFs) or strain frequency response function (SFRF). SAI is calculated by using the acceleration and dynamic strain responses acquired from intact and damaged states of the structure. In a bi-level damage identification algorithm, first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Dilena et al [68] presented the interpolation damage detection method using FRF measurements. Lee and Kim [69] proposed the signal anomaly index to express the amount of changes in the shape of FRFs or strain frequency response function (SFRF). Kim and Eun [70] compared the FRF-based approach extracted from dynamic measurements of a truss structure and the flexibility-based approach extracted from the modal data, and showed that the FRF-based approach can be utilized more explicitly than the flexibility-based approach.…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…Dilena et al [68] presented the interpolation damage detection method using FRF measurements. Lee and Kim [69] proposed the signal anomaly index to express the amount of changes in the shape of FRFs or strain frequency response function (SFRF). Kim and Eun [70] compared the FRF-based approach extracted from dynamic measurements of a truss structure and the flexibility-based approach extracted from the modal data, and showed that the FRF-based approach can be utilized more explicitly than the flexibility-based approach.…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…By comparing the FRFs of a sensing membrane with and without cell attachment, we can identify the features of adhesive cells. Many researchers have successfully employed neural networks on the measued FRF data for structural health monitoring and damage detection [11,12,13,14]. This paper presents the successful cell monitoring application.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, a large amount of data representing the analysed problem is normalized in function of a mapping technique, leading to a faster training of the neural network and improved identification results. For more details refer to [4,6,12].…”
Section: Slanted Crack Identificationmentioning
confidence: 99%